2023
DOI: 10.1007/jhep06(2023)033
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives for testing electron-muon universality

Abstract: Intriguing results for tests of the universality of electrons and muons through measurements of rates of B → Kℓ+ℓ− and similar decays have been in the spotlight for years. The LHCb collaboration has recently reported new results which are in agreement with Lepton Flavour Universality, while the individual decay rates are found below their Standard Model predictions. In view of this new situation, we explore how much space is left for a violation of electron-muon universality. Considering new sources of CP viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A detailed study of the space left by the current data was performed in Ref. [83]. Interestingly, allowing for new CP-violating effects, it was demonstrated that significant differences between the Wilson coefficients of the electronic and muonic final states are still allowed.…”
Section: Rare B Decaysmentioning
confidence: 98%
See 2 more Smart Citations
“…A detailed study of the space left by the current data was performed in Ref. [83]. Interestingly, allowing for new CP-violating effects, it was demonstrated that significant differences between the Wilson coefficients of the electronic and muonic final states are still allowed.…”
Section: Rare B Decaysmentioning
confidence: 98%
“…In semileptonic decays of the kind B → K + − and B → K * + − , B s → φ + − , CP violation can also be explored through a variety of observables [76][77][78][79][80][81][82][83]. In these channels, we get contributions from cc resonances through intermediate J/ψ, ψ(2S), .…”
Section: Rare B Decaysmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in the analysis in Ref. [33] due to new CP-violating effects, there is still significant room for violation of the electron-muon universality. More specifically, this analysis explores the CP-violating effects in the NP studies of rare decays making use of the muonic Wilson coefficients.…”
Section: Topic 4: Cp Violation In Rare Decays What About 𝑅 𝐾 ( * ) An...mentioning
confidence: 99%